2018
DOI: 10.1371/journal.pone.0205918
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol eliminates cancer stem cells of osteosarcoma by STAT3 pathway inhibition

Abstract: Resveratrol shows potent anti-tumor therapeutic properties in various tumors. However, the exact effect of resveratrol on osteosarcoma cells, especially cancer stem cells, remains unclear. In this study, we examined the effect of resveratrol on osteosarcoma stem cells and explored the underlying molecular mechanisms. Resveratrol inhibited cell viability, self-renewal ability and tumorigenesis of osteosarcoma cells, whereas showed no significant inhibition effects to normal osteoblast cells. Mechanically, resve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 39 publications
(37 reference statements)
6
47
0
1
Order By: Relevance
“…Here, our results revealed that BD exhibited the capacity to inhibit the stem cell like traits of osteosarcoma cells and inhibit OSCs self‐renewal ability. Previous studies have reported that STAT3 activation was important in maintaining CSCs, and inhibition of STAT3 signaling may be involved in CSCs stemness attenuation . Consistent with these findings, we found that BD could deactivate STAT3 signaling and inhibition of STAT3 using Stattic significantly suppressed the sphere‐forming and self‐renewal capacity of osteosarcoma cells.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Here, our results revealed that BD exhibited the capacity to inhibit the stem cell like traits of osteosarcoma cells and inhibit OSCs self‐renewal ability. Previous studies have reported that STAT3 activation was important in maintaining CSCs, and inhibition of STAT3 signaling may be involved in CSCs stemness attenuation . Consistent with these findings, we found that BD could deactivate STAT3 signaling and inhibition of STAT3 using Stattic significantly suppressed the sphere‐forming and self‐renewal capacity of osteosarcoma cells.…”
Section: Discussionsupporting
confidence: 90%
“…The data showed that BD stimulation reduced β ‐catenin expression in MNNG/HOS cells (Figure I). It has been reported that STAT3 signaling repression was implicated in resveratrol induced elimination of OSCs . Our results consistently showed that inhibition of STAT3 signaling using Stattic, significantly inhibits sphere formation and self‐renewal ability of OSCs (Figure B,D,F).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, treating gastric cancer cells with resveratrol elevated the levels of pro-apoptotic proteins such as Bax, while the levels of anti-apoptotic proteins such as Bcl-2 were decreased compared to untreated controls . Treatment of osteosarcoma cells with 20 μM resveratrol results in reduction of cell viability, decrease in self-renewing and tumorigenesis via inhibition of intracellular STAT3 signaling and cytokine synthesis (Peng & Jiang, 2018). In general, the anti-cancer activity of resveratrol is based on the suppression of the expression of proteins involved in carcinogenesis, such as phospholipid scramblase 1 , stimulation of caspase 3 cleavage (Lucas et al, 2018) and activation of the mitochondrial ROS signaling pathway (Zheng et al, 2018).…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…It has been proposed that a common gene expression program underpins both cancer and stemness. Consistent with this hypothesis, it has been shown that STAT3 is required to maintain stemness in many different tumors [34,35,[64][65][66][67][68][69][70][71][72][73][74][75][76][77]. At least in breast cancer, a critical mechanism stimulated by STAT3 to regulate stemness involves genes in fatty acid oxidation [72,73] and the ability of STAT3 to adjust the ROS levels produced in mitochondria [73].…”
Section: Reprogramming and Stemnessmentioning
confidence: 89%